Research on the development of an energy technology plant for burning shale gas with the release of useful components - Yayra D. Muхiddinova (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the article considers the possibility of creating an energy technology plant for processing oil shale, which will allow producing liquid and gaseous hydrocarbons from oil shale that are similar in composition and properties to petroleum products and natural gas, which will be important strategic resources. Purpose: the research done and the proposals formulated in can be reflected in real activities to implement the use of the development of an energy technology scheme for processing and burning oil shale (OSh) to produce, which will ensure stable, reliable operation of the national energy system and save on organic fuels. Methods: the study and analysis of the process of semi-coking of oil shales in a fluidized bed reactor, as well as the development of a method for thermal engineering calculation of tubular devices of pyrogasifier reactors with a fluidized bed. Results: the requirements of modern solid fuel pyrogasification technologies can be most successfully implemented using flow-through tubular reactors of the circulating fluidized bed type, the main advantage of which is the possibility of supplying a large amount of heat from an external source through the wall into the reaction zone. Tubular type pyrogasifier reactors have significantly lower unit design costs and are more compact compared to fluidized bed reactors with equal capacity.